The Mount Mary Grotto - Mumbai Archive Project Team (Jio Institute, 2024)
The Mount Mary Grotto, officially known as the Oratory of Our Lady of Fatima, stands facing Mount Mary Basilica across Mount Mary Road. Adorning the walls of the oratory is the sevenfold message of Our Lady of Fatima, encompassing prayer, penance, meditation, peace, rosary, reparation, and sacrifice.